Real-world experiences of CNS-directed chemotherapy followed by autologous stem cell transplantation for secondary CNS involvement in relapsed or refractory diffuse large B-cell lymphoma - Jeong, Sun Young; Yoon, Sang Eun; Cho, Duck; Kang, Eun Suk; Cho, Junhun; Kim, Won Seog; Kim, Seok Jin (Frontiers in Oncology, 2023)
Secondary central nervous system (CNS) involvement is a rare but fatal event in patients with diffuse large B cell lymphoma (DLBCL). Some studies have suggested autologous stem cell transplantation (ASCT) for patients responding to salvage therapies, although its role is not clear. We analyzed DLBCL patients with secondary CNS involvement who received salvage therapies with curative intent and who underwent high-dose chemotherapy followed by ASCT. We analyzed the post-ASCT outcome in terms of CNS and/or systemic relapse and overall survival (OS) according to type of secondary CNS involvement and salvage treatment. A total of 43 patients who achieved complete or partial response after salvage treatments, mainly high-dose methotrexate (MTX)-containing chemotherapy, was treated with busulphan-thiotepa followed by ASCT between 2009 to 2019. Fifteen patients experienced grade III/IV febrile neutropenia, but all adverse events were manageable. After ASCT, 17 patients did not relapse, however, 26 patients had relapsed, comprising isolated CNS relapse (n = 12), systemic relapse (n = 12), and both (n = 2). Patients with systemic relapse had significantly shorter OS than those with isolated CNS relapse (42.7 vs, 11.1 months, p = 0.002). Of the 26 patients who relapsed after ASCT, six patients were rescued by subsequent salvage treatments. Finally, 21 patients were alive at the time of analysis. In conclusion, consolidative ASCT might be beneficial for secondary CNS involvement in relapsed or refractory DLBCL patients if they responded to CNS-directed salvage chemotherapy and were eligible for transplantation.